New fluid and lithology indicator from seismic and rock physics: Malaysian offshore case study - Hermana, M. (Society of Exploration Geophysicists, 2016)
Separation of Lithology from porefill uniquely remains a daunting task even using Elastic Inversion. This is a problem in many of our QI studies in the Malaysian basin for Hydrocarbon prediction. This is because of complexities in lithological trends and fluid response and the so called ambiguity in prediction because of the so called "Equivalence "issue. This paper addresses this problem in coming out with a transformation where this separation can be achieved. From elastic Inversion output we derive a relationship of Vp/Vs and new attribute (SQp & SQs) related to Attenuation concept by linking through Rock physics. They are good proxy for Gamma ray (SQp)and resistivity log (SQs) and can clearly can identify zone of interest of hydrocarbon potential. We further demonstrate that these attribute can be used for petrophysical properties prediction with high accuracy. Â© 2016 SEG.